Pengembangan Bahan Ajar Interaktif Pada Kurikulum Merdeka Berbasis Genially Dalam Materi Administrasi Pajak Kelas XI Akuntansi Keuangan Lembaga SMK Negeri Surabaya - Putra, Venando Aditya; Susanti, Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This research aims to produce interactive teaching materials in the independent curriculum based on Genially, describe the feasibility of interactive teaching materials using Genially, and analyze student responses after testing the developed teaching materials. This type of research is development research with a 4D model, where this research is carried out through four stages, namely: define, design, develop, and disseminate. The interactive teaching materials developed are reviewed and validated first by material experts, language experts and media experts. The trial was carried out on 30 class XI Accounting students from SMK Negeri Surabaya. The results of this research indicate that genially based interactive teaching materials on tax administration subjects are suitable for use. The feasibility of the material validation results is 91.05% in the very feasible category, the feasibility of the language validation results is 98.66 percent in the very feasible category, the feasibility of the media validation results is 84.06 percent in the very feasible category, and the feasibility of the student response results was 98.33% which showed a positive response.